Arousal transmission and attenuation in mother–daughter dyads during adolescence. Issue 1 (7th June 2017) - Lougheed, Jessica P.; Hollenstein, Tom
Abstract: Load sharing is the process through which the emotional burdens associated with challenging situations are distributed among members within close relationships. One indicator of load sharing is efficient emotion regulation, and load sharing is related to high physical and relationship closeness between partners. The purpose of the current study was to examine load sharing in mother–daughter dyads across different emotion contexts during adolescence. We examined load sharing via mothers' and daughters' electrodermal activity, which indicates sympathetic nervous system arousal. Sixty‐six adolescent girls ( M age  = 15.15 years) and their mothers participated in two 4‐min discussions, about negative and positive emotional experiences. Mothers and daughters self‐reported relationship closeness, and physical closeness was experimentally manipulated by randomly assigning mothers to either touch or not touch their daughter's hand during the discussions. Evidence of load sharing was observed for both mothers and daughters in terms of lower arousal levels and greater arousal transmission (i.e., picking up on partners' arousal) at greater physical and relationship closeness, although the specific pattern of results differed for mothers and daughters and across emotion contexts. Taken together, the results of this study demonstrate that load sharing is an important interpersonal dynamic in mother–daughter dyads during adolescence.